A kind of nano-reinforced shrapnel steel and the cold-formed shrapnel shell made of it, and the preparation method of the two products
By combining a nano-reinforced grenade steel preparation method with ultra-low temperature gradient fine-grain solidification and multi-pass cold extrusion process, the problems of high cost and insufficient performance of traditional grenade shell materials have been solved. This has enabled the preparation of cold-formed grenade shells with high strength, toughness and good crushing performance, reducing production costs and shortening the manufacturing cycle.
Patent Information
- Application Number
- CN202310491280.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-04
- Publication Date
- 2025-11-25
- Estimated Expiration
- 2043-05-04
AI Technical Summary
Existing grenade casing materials are costly and have insufficient performance in traditional thermoforming processes, making it difficult to meet the requirements for high strength, toughness, and fragmentation performance. Cold-formed materials have low strength and poor fragmentation, failing to meet the requirements for high overload and fragmentation rate.
Using nano-reinforced grenade steel, a high-strength and tough cold-formed grenade shell is prepared by scientifically matching chemical composition and ultra-low temperature gradient fine-grain solidification technology, combined with solution treatment and multi-pass cold extrusion process. The crushing performance is improved by utilizing the combined effect of deformation-induced martensite and nanoparticles.
It has enabled low-cost and high-efficiency preparation of grenade casings, improved the strength and fragmentation performance of the casings, met the requirements for high-performance grenades, and shortened the manufacturing cycle.
Smart Images

Figure CN116815049B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of cold forming preparation of grenade shell, and particularly relates to a nano-strengthened grenade steel, a cold-formed grenade shell prepared from the nano-strengthened grenade steel and a preparation method of the two products. BACKGROUND
[0002] A grenade is a kind of shell that relies on fragments and shock waves generated after the explosion of explosives to kill or destroy targets, and is the most widely used and used main type of ammunition. The grenade mainly uses fragments to kill and also has the function of blasting, and can effectively attack various targets on the ground, in the air and on the water.
[0003] A warhead is one of the main components of a grenade and is the final damage unit of various ammunition and missiles to damage targets, and mainly comprises a shell, a combat charge, an ignition device and a safety device. In the design of the warhead, the material selection of the grenade shell is an important factor for determining the power and damage efficiency of the warhead. This is because the grenade mainly uses fragments and explosion shock waves as the main damage load, and the killing distance of the fragments is much greater than the coverage range of the explosion shock waves, and the contribution to the damage efficiency is greater. Therefore, improving the fragment killing power is the core and key to improving the overall power of the grenade. The number of effective fragments of the high-speed fragment group generated by the explosion of the grenade and the distribution range of the fragments determine the damage ability of the grenade to targets. Among them, the distribution range of the fragments is determined by the initial distribution direction of the fragments, and is mainly affected by the shape and structure of the shell and the initiation mode of the charge, and the number of effective fragments is mainly determined by the material of the grenade shell. In the design of the grenade, the shape, structure and initiation mode of the charge of the shell are usually restricted by the launch platform, fuze and the like, and are difficult to change easily. Therefore, by changing the material of the grenade shell to increase the number of effective fragments, an important way to improve the power of the grenade has been found.
[0004] In addition, the design of the grenade needs to consider the use requirements of harsh launch conditions and special action environments, as well as the application of new generation high-energy explosives. Combining the above factors, it can be found that the ideal grenade shell should have high strength and high toughness while having excellent fragmentation effect.
[0005] The traditional manufacturing process of a shell of a shrapnel is hot forming steel, and the shrapnel shell fragment killing power is closely related to the material selection, material organization and performance. In the traditional shrapnel shell material, the material used in the shrapnel shell is a series of high-strength and high-fragment-rate shrapnel steels represented by 15MnPV, 20MnTi, 60Si2Mn and 58SiMn, wherein the fragment rate of the 58SiMn steel is much higher than that of the D60. On the basis of the research on the 58SiMn steel, a new generation of shrapnel steel 50SiMnVB widely used in the manufacture of natural fragment warheads is obtained, and the yield strength of the 50SiMnVB steel is increased from 800 MPa of the 58SiMn steel to 1000 MPa. The 50SiMnVB steel has good comprehensive mechanical properties, but the fragment rate is lower than that of the 58SiMn. The above-mentioned shrapnel shell materials mainly obtain good fragment effect by containing a high content of carbon, silicon and manganese in the steel, so that the ammunition can effectively damage the living forces, weapon equipment and facilities within a certain range. These materials are mainly prepared by the hot forming process with high production cost. However, the traditional hot forming preparation process has a long process flow, and the material loss caused by hot working cutting is large, so the cost of producing one shrapnel shell by the hot forming process is very high.
[0006] With the development of manufacturing process and the gradual improvement of performance requirements such as weapon range and power, in order to reduce the production cost, the researchers in the field have invested in the research on the preparation of a new cold-formed shrapnel shell. At present, the cold-formed shrapnel steel mainly adopts 10 steel and 20 steel with ferrite as the main organization. These low-carbon ferrite steels have low strength and poor fragmentation, and the performance cannot meet the use requirements of high overload and fragment rate of most shrapnels. Therefore, it is urgent to develop a new shrapnel steel with excellent cold formability, high strength and toughness and good fragmentation performance. SUMMARY
[0007] The purpose of the present application is to provide a nano-reinforced shrapnel steel and a cold-formed shrapnel shell prepared therefrom.
[0008] In order to achieve the above-mentioned purpose, the present application provides the following technical solutions.
[0009] A nano-reinforced shrapnel steel, wherein the shrapnel steel contains the following chemical components in the following weight percentages:
[0010]
[0011]
[0012] The balance is iron and other unavoidable impurities.
[0013] The present application provides a preparation method of the nano-reinforced shrapnel steel, comprising the following steps:
[0014] Step 1): mixing the metal raw materials Fe, Ni, W, Cr and melting under vacuum;
[0015] Step 2): adding the remaining raw materials except Al into the melting product of Step 1) first, and then adding aluminum wire to obtain an alloy molten liquid and detect the chemical composition in the alloy molten liquid;
[0016] Step 3): repeating Step 2) until the chemical composition in the alloy molten liquid meets the requirements to obtain the required steel liquid;
[0017] Step 4): injecting the steel liquid prepared in Step 3) into a mold and performing ultra-low temperature gradient fine-grain solidification casting to obtain the nano-strengthened shrapnel steel after cooling.
[0018] Optionally, the melting process in Step 1) comprises heating at a power of 20-40 kW, increasing the power to 50-160 kW when the metal starts to melt, melting to spatter, and reducing the power to 100-120 kW.
[0019] Optionally, the ultra-low temperature gradient fine-grain solidification casting in Step 4) has a revolution speed of 10-30 r / min, a revolution speed ratio of the revolution position to the rotation position of 1:0.5-0.75, and a time of 40-80 min.
[0020] The application further provides a method for preparing a cold-formed shrapnel shell body using the nano-strengthened shrapnel steel, comprising the following steps:
[0021] solid solution treatment of the nano-strengthened shrapnel steel, followed by multiple cold extrusion forming and aging treatment to obtain the cold-formed shrapnel shell body.
[0022] Optionally, the solid solution treatment has a temperature of 950-1100 ℃ and a time of 1-2 h.
[0023] Optionally, the multiple cold extrusion forming specifically comprises 3-5 times of cold extrusion, and the total extrusion deformation amount in the cold extrusion forming process is 30-90%.
[0024] After each cold extrusion, annealing treatment at 200-350 ℃ for 0.5-2 h is required.
[0025] Optionally, the aging treatment is at 450-550 ℃ for 2-3 h.
[0026] The application further provides a cold-formed shrapnel shell body prepared from the nano-strengthened shrapnel steel.
[0027] The research finds that the austenite structure of the steel has good plasticity and toughness, and the composition of the steel is uniform after the ultra-low temperature gradient fine-grain solidification casting, and the steel has good cold forming performance. On this basis, the required shell of the grenade can be directly prepared by combining the solid solution treatment and the multi-pass cold extrusion. The shell of the grenade is subjected to the corresponding aging treatment after the forming, and the high strength and toughness required by the shell of the grenade are met.
[0028] The good breaking effect of the shell of the grenade is realized by the deformation-induced martensite formed in the cold forming process and the nano-particles dispersed in the matrix formed in the aging process.
[0029] By scientifically matching the chemical composition of the grenade steel (such as C, Mn, Cr, Ni, Mo, W, Al and the like), it is ensured that the as-cast structure of the ingot of the grenade steel is austenite, and the ultra-low temperature gradient (-200℃ / m~200℃ / m) fine-grain solidification technology is used to ensure that the composition and structure of the ingot are uniform, and the cold forming performance is improved. After the solid solution treatment, the yield strength R el ≤350MPa, and the elongation A≥40%. On this basis, the shell of the grenade is prepared by using the grenade steel through the multi-pass cold extrusion process of the cold extrusion equipment. The multi-pass is 3~5 passes of cold extrusion in a step deformation mode of pre-deformation, medium deformation and large deformation to meet the total deformation requirement, and the low-temperature annealing treatment is performed on the grenade steel after each cold extrusion. The grain structure in the interior of the grenade steel can be refined and uniformly distributed after the cold extrusion and the annealing treatment. After the extrusion deformation of 30%~90% is completed according to the performance requirement, the required shell of the grenade is prepared. The shell of the grenade is subjected to the aging treatment, and the nano M2C type eutectic carbide and intermetallic compound are formed in the aging process. The strength (tensile strength R m ≥1200MPa, and the elongation A≥9%) of the shell of the grenade is improved by the matrix nano M2C type eutectic carbide and intermetallic compound and the martensite structure contained in the matrix, and the breaking performance is improved. The cold forming performance, the high strength and toughness and the breaking performance of the grenade steel are scientifically matched in the present application, and the operability is strong. Compared with the traditional long process hot forming process, the cost is low, the energy is saved, and the manufacturing cycle of the shell of the grenade is shortened, and the present application can be applied to the industrialized batch production. BRIEF DESCRIPTION OF DRAWINGS
[0030] Figure 1 The preparation flow chart of the nano-strengthened grenade steel and the cold formed shell of the grenade is shown in the present application.
[0031] Figure 2 The nano-strengthened grenade steel prepared in Example 1 of the present application is shown in the present application.
[0032] Figure 3The as-cast microstructure diagram of the nano-reinforced grenade steel prepared in Embodiment 1 of the present application;
[0033] Figure 4 The ultra-low temperature gradient fine-grain solidification casting device diagram according to the present application;
[0034] Figure 5 The technical schematic diagram of the ultra-low temperature gradient fine-grain solidification casting process according to the present application. DETAILED DESCRIPTION
[0035] The present application provides a nano-reinforced grenade steel, the components of the grenade steel contain the following chemical components in percentage by weight:
[0036]
[0037]
[0038] The balance is iron and other inevitable impurities.
[0039] In the present application, the content of C element in the grenade steel is 0.05-0.20%, preferably 0.07-0.18%, further preferably 0.10-0.15%;
[0040] The content of Si element in the grenade steel is 0.10-0.20%, preferably 0.12-0.18%, further preferably 0.14-0.16%;
[0041] The content of Mn element in the grenade steel is 1.0-10.0%, preferably 2.0-9.0%, further preferably 4.0-8.0%, more further preferably 5.0-7.5%;
[0042] The content of Cr element in the grenade steel is 3.0-18.0%, preferably 4.0-15.0%, further preferably 6.0-12.0%, more further preferably 8.0-10.0%;
[0043] The content of Ni element in the grenade steel is 5.0-12.0%, preferably 6.0-11.0%, further preferably 7.0-10.0%, more further preferably 8.0-9.0%;
[0044] The content of Mo element in the grenade steel is 0-3.0%, preferably 0.5-2.5%, further preferably 1.0-2.0%, more further preferably 1.2-1.5%;
[0045] The content of Nb element in the grenade steel is 0-0.05%, preferably 0.01-0.04%, further preferably 0.02-0.03%;
[0046] The content of V in the grenade steel is ≤0.10%, preferably 0.02-0.09%, further preferably 0.04-0.08%, and more preferably 0.05-0.06%;
[0047] The content of W in the grenade steel is ≤0.10%, preferably 0.01-0.09%, further preferably 0.03-0.07%, and more preferably 0.04-0.06%.
[0048] The content of Al in the grenade steel is 0.2-1.2%, preferably 0.4-1.0%, further preferably 0.5-0.9%, and more preferably 0.6-0.8%.
[0049] The application provides a preparation method of the nano-reinforced grenade steel, comprising the following steps:
[0050] Step 1): mixing metal raw materials Fe, Ni, W and Cr and melting under vacuum;
[0051] Step 2): adding the remaining raw materials except Al into the melting product of step 1), and then adding aluminum wire to obtain an alloy molten liquid and detect the chemical composition in the alloy molten liquid;
[0052] Step 3): repeating step 2) until the chemical composition in the alloy molten liquid meets the requirements to obtain the required steel liquid;
[0053] Step 4): injecting the steel liquid prepared in step 3) into a mold and performing ultra-low temperature gradient fine-grain solidification casting, and obtaining the nano-reinforced grenade steel after cooling.
[0054] In the application, the melting process of step 1) comprises heating at a power of 20-40 kW, preferably 25-36 kW, further preferably 28-32 kW; when the metal starts to melt, the power is increased to 50-160 kW, preferably 70-150 kW, further preferably 80-135 kW, and more preferably 95-120 kW to melt until spattering occurs, and then the power is reduced to 100-120 kW, preferably 105-115 kW, and further preferably 110 kW.
[0055] In the application, before the steel liquid is injected into the mold, the temperature of the steel liquid needs to be increased to the tapping temperature, which is 30-50°C, preferably 35-45°C, and further preferably 40°C higher than the melting point of the steel liquid.
[0056] In the present application, the ultra-low temperature gradient fine-grain solidification casting in step 4) can be completed by complex shearing, the revolution speed of the process is 10-30 r / min, preferably 12-28 r / min, further preferably 15-25 r / min, and more further preferably 18-20 r / min; the revolution speed ratio of the revolution position and the rotation position is 1:0.5-0.75, preferably 1:0.55-0.7, and further preferably 1:0.6-0.65; the time of complex shearing is 40-80 min, preferably 45-75 min, further preferably 50-70 min, and more further preferably 55-65 min.
[0057] The present application also provides a method for preparing a cold-formed shell of a shrapnel using the nano-reinforced shrapnel steel, comprising the following steps:
[0058] The nano-reinforced shrapnel steel is subjected to solid solution treatment, then subjected to multiple cold extrusion forming and aging treatment to obtain the cold-formed shell of the shrapnel.
[0059] In the present application, the temperature of the solid solution treatment is 950-1100℃, preferably 970-1070℃, further preferably 1000-1050℃, and more further preferably 1010-1040℃; and the time is 1-2 h, preferably 1.2-1.8 h, and further preferably 1.5 h.
[0060] In the present application, the multiple cold extrusion forming is specifically 3-5 times of cold extrusion, preferably 4 times of cold extrusion; and the total extrusion deformation amount in the cold extrusion forming process is 30-90%, preferably 40-80%, further preferably 45-70%, and more further preferably 50-60%.
[0061] After each cold extrusion is completed, annealing treatment at 200-350℃, preferably 250-320℃, and further preferably 280-300℃ for 0.5-2 h, preferably 1-1.5 h is required.
[0062] In the present application, the aging treatment is at 450-550℃, preferably 480-540℃, and further preferably 500-520℃; and the holding time is 2-3 h, preferably 2.2-2.8 h, and further preferably 2.5 h.
[0063] The present application also provides a cold-formed shell of a shrapnel prepared from the nano-reinforced shrapnel steel.
[0064] In the present application, small pieces of metal should be placed at the bottom of the container before smelting, and large pieces of metal should be woven at the upper part of the container, so as to ensure that the inside of the container is tight at the bottom and loose at the top, thereby avoiding the occurrence of "bridge" accidents during the metal melting process.
[0065] In the present application, the purpose of adding the aluminum wire alone is to deoxidize and control the oxygen content.
[0066] The technical solutions provided by the present application are described in detail below in combination with examples, but they should not be understood as limiting the scope of protection of the present application.
[0067] Example 1
[0068] 1) The raw materials are weighed according to C 0.08 kg, Si 0.19 kg, Mn 2.4 kg, Cr 24 kg, Ni 12.8 kg, Nb 0.032 kg, V 0.08 kg, W 0.08 kg, Al 1.12 kg, and Fe 119.22 kg, wherein Ni, W, and Cr are pure metals, Si, Mn, Nb, and V are alloys of the element and Fe, Fe is the total of the iron element content in the alloy and pure iron, Al is an aluminum wire with a diameter of 1.5 mm, and C is an electrode powder;
[0069] 2) The pure metals Fe, Ni, W, and Cr are placed at the bottom of the crucible as high-melting-point and small-block metals, and the large-block metals are placed at the upper part of the crucible to ensure that the inside of the crucible is tight at the bottom and loose at the top after being loaded into the furnace;
[0070] 3) The furnace cover is closed, the mechanical pump is started, and the vacuum degree reaches 1000 Pa within 10 min, and then the Roots pump is started, and the vacuum degree reaches 10 Pa within 15 min;
[0071] 4) The intermediate frequency power supply is started, the melting furnace power is set to 20 kW, the temperature is raised by electricity, and when the metal in the crucible starts to melt, the power is increased to 60 kW for melting;
[0072] 5) The power is reduced to 100 kW when spattering occurs, and the vacuum pump is turned off;
[0073] 6) The remaining raw materials except aluminum are added, the sealing wire feeding mechanism added to the vacuum induction furnace cover is used to add secondary materials into the crucible, the aluminum wire is fed into the alloy liquid for deoxidization and oxygen content control, and after the melting is clear, the chemical composition is detected by sampling;
[0074] 7) Step 6) is repeated until the chemical composition in the alloy molten liquid meets the requirements, and the required steel liquid is obtained;
[0075] 8) Then, the temperature of the steel liquid is measured by a temperature measuring device, and the steel liquid is adjusted to the tapping temperature (40℃ higher than the melting point). After the steel liquid temperature reaches the tapping requirement, the composition and temperature meet the requirements, and the pouring is carried out. After the steel liquid in the crucible enters the ingot mold, the composite shear flow device is started to make the solidification process reach the ultra-low temperature gradient and refine the ingot structure. The test parameters are as follows: the revolution direction is counterclockwise, the speed is 20 r / min, the rotation direction is clockwise, the revolution ratio and the rotation ratio are 1:0.5, and the shear flow device is stopped after running for 60 min;
[0076] 9) After pouring is completed, cooling is performed, then a gas release valve is opened to break the vacuum, a furnace door is opened, and a crown block is used to lift out the ingot mold; the ingot mold is moved to a mold stripping area using the crown block, and the mold is stripped to obtain the nano-strengthened grenade steel.
[0077] Example 2
[0078] 1) Raw materials are weighed according to C 0.128 kg, Si 0.192 kg, Mn 6.4 kg, Cr 17.6 kg, Ni 16 kg, Mo 1.6 kg, V 0.096 kg, W 0.08 kg, Al 1.12 kg, and Fe 116.78 kg, wherein Ni, W, and Cr are pure metals, Si, Mn, Mo, and V are alloys of the elements and Fe, the total of the iron element content in the alloy and pure iron, and Al is aluminum wire with a diameter of 2 mm, and C is an electrode powder;
[0079] 2) Fe, Ni, W, and Cr are placed at the bottom of the crucible as high-melting-point and small-block metals, and large-block metals are placed at the upper part of the crucible, to ensure that the inside of the crucible is tight at the bottom and loose at the top after loading;
[0080] 3) The furnace cover is closed, the mechanical pump is started, and the vacuum degree reaches 1000 Pa within 10 min, and then the Roots pump is started, and the vacuum degree reaches 10 Pa within 15 min;
[0081] 4) The intermediate frequency power supply is started, the power of the smelting furnace is set to 30 kW, the temperature is raised by electricity, and when the metal in the crucible starts to melt, the power is increased to 100 kW for melting;
[0082] 5) When spitting occurs, the power is reduced to 105 kW, and the vacuum pump is turned off;
[0083] 6) The remaining raw materials except for aluminum are added, the sealed wire feeding mechanism added to the vacuum induction furnace cover is used to add secondary materials to the crucible, and aluminum wire is fed into the alloy liquid for deoxidation and oxygen content control. After melting, the chemical composition is detected by sampling;
[0084] 7) Step 6) is repeated until the chemical composition of the alloy molten liquid meets the requirements, and the required steel liquid is obtained;
[0085] 8) Then, the temperature of the steel liquid is measured using a temperature measuring device, and the steel liquid is adjusted to the tapping temperature (50°C higher than the melting point). After the steel liquid temperature reaches the tapping requirement, the composition and temperature meet the specified requirements, and pouring is performed. After the steel liquid in the crucible enters the ingot mold, the composite shear flow device is started to make the solidification process reach an ultra-low temperature gradient and refine the ingot structure. The test parameters are as follows: the revolution direction is counterclockwise, the speed is 20 r / min, the rotation direction is clockwise, the revolution ratio and rotation ratio are 1:0.75, and the shear flow device is stopped after running for 60 min;
[0086] 9) After pouring is completed, cooling is performed, then a gas release valve is opened to break the vacuum, a furnace door is opened, and a mold is lifted out using a crane; the mold is moved to a mold removal area using the crane, and the mold is disassembled to obtain the nano-strengthened grenade steel.
[0087] Example 3
[0088] 1) Raw materials are weighed according to C 0.192 kg, Si 0.32 kg, Mn 12.8 kg, Cr 6.4 kg, Ni 16 kg, Mo 3.2 kg, Nb 0.04 kg, V 0.128 kg, W 0.08 kg, Al 1.6 kg, and Fe 119.24 kg, wherein Ni, W, and Cr are pure metals, Si, Mn, Mo, Nb, and V are alloys of the element and Fe, Fe is the total of the iron element content in the alloy and pure iron, Al is aluminum wire with a diameter of 3 mm, and C is electrode powder;
[0089] 2) Fe, Ni, W, and Cr are placed at the bottom of the crucible as high-melting-point and small-block metals, and large-block metals are placed at the upper part of the crucible to ensure that the inside of the crucible is tight at the bottom and loose at the top after being loaded into the furnace;
[0090] 3) The furnace cover is closed, the mechanical pump is started, and the vacuum degree reaches 1000 Pa within 10 min, and then the Roots pump is started, and the vacuum degree reaches 10 Pa within 15 min;
[0091] 4) The intermediate frequency power supply is started, the power of the smelting furnace is set to 40 kW, the temperature is raised by electricity, and when the metal in the crucible starts to melt, the power is increased to 140 kW for melting;
[0092] 5) When spitting occurs, the power is reduced to 115 kW, and the vacuum pump is turned off;
[0093] 6) The remaining raw materials except aluminum are added, the sealed wire feeding mechanism added to the vacuum induction furnace cover is used to add secondary materials to the crucible, and aluminum wire is fed into the alloy liquid for deoxidation and oxygen content control. After melting, the chemical composition is detected by sampling;
[0094] 7) Step 6) is repeated until the chemical composition of the alloy molten liquid meets the requirements, and the required steel liquid is obtained;
[0095] 8) Then, the temperature of the steel liquid is measured by a temperature measuring device, and the steel liquid is adjusted to the tapping temperature (50°C higher than the melting point). After the steel liquid temperature reaches the tapping requirement, the composition and temperature meet the specified requirements, and then pouring is performed. After the steel liquid in the crucible enters the ingot mold, the composite shear flow device is started to make the solidification process reach an ultra-low temperature gradient and refine the ingot structure. The test parameters are as follows: the revolution direction is counterclockwise, the speed is 20 r / min, the rotation direction is clockwise, the revolution ratio and rotation ratio are 1:0.75, and the shear flow device is stopped after running for 60 min.
[0096] 9) After pouring is completed, cooling down, then open the exhaust valve to break the vacuum, open the furnace door, using the crane to lift out the ingot mold; using the crane to move the ingot mold to the mold removal area, and then remove the mold to obtain the nano-strengthened shrapnel steel.
[0097] Example 4
[0098] The nano-strengthened shrapnel steel prepared in Example 1 is subjected to solid solution treatment, specifically, heat preservation at 950℃ for 1h; then, 3 times of cold extrusion process is adopted to make it reach 40% of total deformation, and after each cold extrusion is completed, annealing treatment at 250℃ for 1h is needed, and after cold extrusion is completed, aging treatment is carried out, specifically, heating to 500℃, heat preservation for 3h, to obtain the cold-formed shrapnel shell.
[0099] Example 5
[0100] The nano-strengthened shrapnel steel prepared in Example 2 is subjected to solid solution treatment, specifically, heat preservation at 1050℃ for 2h; then, 4 times of cold extrusion process is adopted to make it reach 60% of total deformation, and after each cold extrusion is completed, annealing treatment at 250℃ for 1h is needed, and after cold extrusion is completed, aging treatment is carried out, specifically, heating to 520℃, heat preservation for 2h, to obtain the cold-formed shrapnel shell.
[0101] Example 6
[0102] The nano-strengthened shrapnel steel prepared in Example 3 is subjected to solid solution treatment, specifically, heat preservation at 1100℃ for 1h; then, 5 times of cold extrusion process is adopted to make it reach 70% of total deformation, and after each cold extrusion is completed, annealing treatment at 250℃ for 1h is needed, and after cold extrusion is completed, aging treatment is carried out, specifically, heating to 550℃, heat preservation for 2h, to obtain the cold-formed shrapnel shell.
[0103] Experimental Example
[0104] The nano-strengthened shrapnel steels prepared in Examples 1-3 are subjected to solid solution treatment, and the yield strength and elongation after fracture of the shrapnel steel in the solid solution state are detected,
[0105] The solid solution treatment condition of the nano-strengthened shrapnel steel prepared in Example 1 is heat preservation at 950℃ for 1h;
[0106] The solid solution treatment condition of the nano-strengthened shrapnel steel prepared in Example 2 is heat preservation at 1050℃ for 2h;
[0107] The solid solution treatment condition of the nano-strengthened shrapnel steel prepared in Example 3 is heat preservation at 1100℃ for 1h.
[0108] The results are shown in Table 1:
[0109] Table 1: Mechanical properties of the nano-reinforced shrapnel steel prepared in Examples 1-3 after solid solution treatment
[0110]
[0111] The cold-formed shrapnel shells prepared in Examples 4-6 were detected, and the results are shown in Table 2.
[0112] Table 2: Mechanical properties of the cold-formed shrapnel shells prepared in Examples 4-6
[0113]
[0114] As shown in Tables 1-2, the yield strength of the nano-reinforced shrapnel steel prepared in Examples 1-3 in solid solution state can reach 287 MPa, and the elongation after fracture can reach 73.5%; the tensile strength of the cold-formed shrapnel shells prepared in Examples 4-6 can reach 1341 MPa, and the elongation after fracture is about 11%, which shows that the shrapnel shells have good performance control and can meet the use requirements. Moreover, the cold forming process is used in the shrapnel shell forming stage, which has low temperature requirement and can save cost.
[0115] The above description is only preferred embodiments of the present application, and it should be pointed out that those skilled in the art can make some improvements and refinements without departing from the principles of the present application, and these improvements and refinements should also be considered as the protection scope of the present application.
Claims
1. A nano-reinforced grenade steel, characterized in that, The grenade steel composition contains the following chemical components by weight percentage: C element 0.05~0.20% Si element 0.10~0.20% Mn element 1.0~10.0% Cr content: 3.0%~18.0% Ni element 5.0~12.0% Mo element 0~3.0% Nb element 0~0.05% V element ≤ 0.10% W element ≤ 0.10% Al element 0.2~1.2% The balance consists of iron and other unavoidable impurities; The preparation method of the nano-reinforced grenade steel includes the following steps: Step 1): Mix the metallic raw materials Fe, Ni, W, and Cr and smelt them under vacuum; Step 2): Add the remaining raw materials other than Al to the smelting product of Step 1), then add aluminum wire to obtain the alloy melt and test the chemical composition of the alloy melt. Step 3): Repeat step 2) until the chemical composition of the alloy melt meets the requirements, and the desired molten steel is obtained; Step 4): The molten steel obtained in Step 3) is injected into the mold and subjected to ultra-low temperature gradient fine-grain solidification casting. After cooling, the nano-reinforced grenade steel is obtained. The temperature gradient for the ultra-low temperature gradient fine-grain solidification casting is -200℃ / m to 200℃ / m; The as-cast microstructure of the nano-reinforced grenade steel is austenitic; Step 4) The revolution speed of the ultra-low temperature gradient fine-grained solidification casting is 10~30 r / min, the speed ratio of the revolution position to the rotation position is 1:0.5~0.75, and the time is 40~80 min.
2. The method for preparing the nano-reinforced grenade steel according to claim 1, characterized in that, Includes the following steps: Step 1): Mix the metallic raw materials Fe, Ni, W, and Cr and smelt them under vacuum; Step 2): Add the remaining raw materials other than Al to the smelting product of Step 1), then add aluminum wire to obtain the alloy melt and test the chemical composition of the alloy melt. Step 3): Repeat step 2) until the chemical composition of the alloy melt meets the requirements, and the desired molten steel is obtained; Step 4): The molten steel obtained in Step 3) is injected into the mold and subjected to ultra-low temperature gradient fine-grain solidification casting. After cooling, the nano-reinforced grenade steel is obtained. The temperature gradient for the ultra-low temperature gradient fine-grain solidification casting is -200℃ / m to 200℃ / m; The as-cast microstructure of the nano-reinforced grenade steel is austenitic.
3. The preparation method according to claim 2, characterized in that, Step 1) The smelting process includes heating with a power of 20~40kW, increasing the power to 50~160kW when the metal begins to melt, and reducing the power to 100~120kW when the metal begins to splash.
4. A method for preparing a cold-formed grenade casing using the nano-reinforced grenade steel of claim 1, characterized in that, Includes the following steps: The cold-formed grenade shell is obtained by solution treatment of nano-reinforced grenade steel, followed by multiple cold extrusion moldings and aging treatment. The multiple cold extrusion molding specifically refers to 3 to 5 cold extrusions, with the total extrusion deformation in the cold extrusion molding process ranging from 30% to 90%. After each cold extrusion, annealing treatment at 200~350℃ is required for 0.5~2 hours.
5. The method for preparing cold-formed grenade casings from nano-reinforced grenade steel according to claim 4, characterized in that, The solution treatment is performed at a temperature of 950~1100℃ for 1~2 hours.
6. The method for preparing cold-formed grenade casings from nano-reinforced grenade steel according to claim 4 or 5, characterized in that, The aging treatment is carried out at 450~550℃ for 2~3 hours.
7. The cold-formed grenade casing obtained by the method for preparing cold-formed grenade casings from nano-reinforced grenade steel according to any one of claims 4 to 6.
Citation Information
Patent Citations
Casting device and method for homogenizing high-temperature alloy structure
CN113523218A
Super-high strength ferritic steel reinforced with nano-intermetallics and manufacturing method thereof
WO2014139451A1